2020
DOI: 10.1101/2020.02.24.20027052
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Clinical and radiographic features of cardiac injury in patients with 2019 novel coronavirus pneumonia

Abstract: Objective: To investigate the correlation between clinical characteristics and cardiac injury of COVID-2019 pneumonia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
65
1
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(70 citation statements)
references
References 8 publications
2
65
1
2
Order By: Relevance
“…The general clinical symptoms found in COVID- 19 suggesting that myocardial inflammation occurred in COVID-19 patients 30 . As the cytokine storm and consequent inflammatory response are suggested to be the mechanisms contributing to myocardial injury, low EAT density showed in chest CT scan appears to be a high-risk factor for myocardial injury.…”
Section: Clinical Symptoms and Profilesmentioning
confidence: 94%
See 1 more Smart Citation
“…The general clinical symptoms found in COVID- 19 suggesting that myocardial inflammation occurred in COVID-19 patients 30 . As the cytokine storm and consequent inflammatory response are suggested to be the mechanisms contributing to myocardial injury, low EAT density showed in chest CT scan appears to be a high-risk factor for myocardial injury.…”
Section: Clinical Symptoms and Profilesmentioning
confidence: 94%
“…The result showed that there was no significant difference in the body temperature correlation with arrhythmia between the mild and severe/critical groups. Many COVID-19 patients with tachycardia are severely ill and need critical care, as tachycardia represents a sign of a failing heart30 .With regard to the imaging features of cardiac injury, the epicardial adipose tissue (EAT) density, a measurement for inflammation, between the bifurcation of pulmonary artery and diaphragm as determined by lung CT scan may serve as a specific indicator for COVID-19-induced myocardial injury. Hui et al reported that the mean EAT density of critical/severe groups in chest CT scan were significantly lower than patients in the light/mild groups (-98.77 /-96.08 HU vs -69.37/-84.76 HU),…”
mentioning
confidence: 99%
“…The severe patients also showed higher creatine kinase-MB (CK-MB) and hypersensitive troponin I (hs-TnI) levels than others 5 . A latest study also reported cardiac injury of COVID-19 was common in severe patients with the peak value of TnI over 40 folds than normal value 6 . However, there is no research concerning whether the heart failure marker, N terminal pro B type natriuretic peptide (NT-proBNP) predicted outcome of COVID-19 patients.…”
Section: Introductionmentioning
confidence: 90%
“…Of an initial cohort of 1,099 hospitalized patients diagnosed with COVID-19, many developed diffuse alveolar damage (DAD) 1 , pneumonia (79.1%), not infrequently complicated by acute respiratory distress syndrome (ARDS, 3.4%), and shock (1.0%), with 5.0% of patients requiring ICU admission and 2.2% requiring ventilation 4 . As the number of patients has surged, multi-system pathologies have been increasingly described, including kidney injury 9 , liver injury, gastrointestinal symptoms 4 , cardiac injury and dysfunction 2,5,10 , and multiorgan failure [1][2][3][4] . In addition to nasal and throat secretions, SARS-CoV-2 RNA has also been detected in saliva and stool specimens 10,11 , suggesting possible alternative routes of transmission beyond respiratory droplets 12, 13 .…”
Section: Introductionmentioning
confidence: 99%
“…As the number of patients has surged, multi-system pathologies have been increasingly described, including kidney injury 9 , liver injury, gastrointestinal symptoms 4 , cardiac injury and dysfunction 2,5,10 , and multiorgan failure [1][2][3][4] . In addition to nasal and throat secretions, SARS-CoV-2 RNA has also been detected in saliva and stool specimens 10,11 , suggesting possible alternative routes of transmission beyond respiratory droplets 12, 13 . SARS-CoV-2 may also infect the testis, similarly to SARS-CoV 14,15 .…”
Section: Introductionmentioning
confidence: 99%